Spatial and temporal characteristics of nighttime UHII based on local climate zone scheme using mobile measurement-A case study of Changsha. (15th January 2023) - Chen, Yaping; Li, Jiayu; Hu, Yinze; Liu, Luyun
Abstract: The local climate varies with time and space because of diversified urban patterns across the complex urban region. Achieving accurate local climatic characteristics by efficient field survey method will contribute to the theoretical and technical reference for urban heat island intensity (UHII) alleviation and eco-friendly environment construction. This study takes the main urban area of Changsha as an example, and focuses on the local-scale UHII characteristics under the Local Climate Zone (LCZ) scheme. An efficient method integrating both the mobile measurement and the GIS-based method is proposed and applied. By applying temporal corrections to the obtained mobile data, the local UHII along the mobile route are expressed. Then based on the UHII values along the mobile route and the LCZ map, a stepwise multiple regression model was built to predict the spatial distributions of UHII within the whole main urban area of Changsha. Results indicated that the built-up LCZs accounted for 42.07% and the land cover LCZs took up 57.93%. The monthly average UHII of Changsha ranged from 1 °C to 4 °C and the core UHII overlayed the city center. The mean UHII of different LCZs ranged from 0.6 °C to 4.8 °C, and the high UHII was more likely to be observed in the compact LCZs. The proposed methodology could be useful for supporting local scale UHII adaptation and mitigation efforts, thus encouraging a more sustainable built environment. Highlights: Generate a LCZ map at a resolution of 250 m. Pedestrian height UHII by mobile measurement at the urban scale. UHII of different LCZs ranged from 0.6 °C to 4.8 °C. High UHII was observed in the compact LCZs.